Аналіз ринку рибної продукції України - Левківська (Музика), Тетяна Миколаївна (My University, 2020)
Проаналізовано стан ринку рибної продукції. Визначено лідери імпортери та експортери рибної продукції. Розглянуто асортимент продуктів та уподобання українців щодо їх споживання. The state of the fish products market is analyzed. Leaders importers and exporters of fish products have been identified. The range of products and preferences of Ukrainians regarding their consumption are considered.
Keywords: риба; рибопродукти; ринок; попит; fish; fish products; market demand; кафедра технології консервування